A K/Ka‐band dielectric and metallic 3D printed aperture shared multibeam parabolic reflector antenna for satellite communication. Issue 7 (2nd March 2020) - Zhu, Xuyi; Zhang, Bing; Huang, Kama
Abstract: A K / Ka ‐band (22‐33 GHz) high‐gain aperture shared multibeam parabolic reflector antenna is proposed. It performs a two‐dimensional beam scanning from a shared single parabolic reflector by introducing off‐focal feeds. The feed array is placed on and off the focal of the parabolic reflector. Traditionally, the feed blockage has a great impact on the performance of the antenna, which reduces the gain and increases the sidelobe level. The purpose of this paper is to suppress the negative effects of feed blockage by using hybrid material processing method. Both dielectric and metallic 3D printing technologies are used for antenna fabrication. The parabolic reflector antenna is printed by selective laser melting using aluminum alloy. The feed array and the supporting structures are printed by stereolithography apparatus in resin to control the blockage. The method helps to suppress the sidelobe level from −10 to −15 dB and to enhance gain by up to 2.3 dBi. The reflection coefficient is less than −10 dB, while the coupling coefficient between the ports is less than −20 dB over the entire designed band. At 31.5 GHz, the simulated maximum gain of the antenna are 30.7, 29.1, and 29.7 dBi, when different port separately excites. Multiple beams at ±15° and 0° are observed on both E ‐ and H ‐planes. Besides, it also verifies the possibility to use dielectric and metallic 3D printing technologies in hybrid for microwave device fabrication.